HUBUNGAN ANTARA TINDAKAN SUPERVISI DENGAN KEPUASAN KERJA: - MIFTAHUL HUDA (Jurnal Bisnis dan Akuntansi, 2000)
The important and significant for academicians is about expectation after college. Their weakness is unbalance between theory and actual knowledge in real work conditions. Through this research, researcher tried to help them to choice their own works. The result for these research about relation between supervisory actions (leadership & mentoring, working, conditions, assignments) and job satisfaction that entry-level accountant tend to increase their satisfaction if joined with big accountant public.